The Effect Of Internet Use In Learning And Counseling Guidance Services On Achievement Appreciating Character Of Catholic High School Students In Tomohon City - Hadi Ignatius Untu; Murtiaty G.M. Sumolang (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to determine the effect of the internet use in learning and counseling guidance services together on the achievement appreciating characters of Catholic High School students in Tomohon City. In this study the method used was quantitative research method with a sample of 276 students obtained using the Slovin formula with a large population of 893 students and using a questionnaire as a research instrument. Testing the hypothesis using Multiple Linear Regression analysis. After the research was carried out, the results obtained were that there was a positive and significant effect on the internet use in learning and counseling guidance services on the achievement appreciating character of Catholic High School students in Tomohon City. The significance value is 0.000 and the effect is 45.4%.